Is Inflation Default? The Role of Information in Debt Crises - Bassetto, Marco; Galli, Carlo (American Economic Review, 2019)
We study the information sensitivity of government debt denominated in domestic versus foreign currency: the former is subject to inflation risk and the latter to default. Default only affects sophisticated bond traders, whereas inflation concerns a larger and less informed group. Within a two- period Bayesian trading game, differential information manifests itself in the secondary market, and we display conditions under which debt prices are more resilient to bad news even in the primary market, where only sophisticated players operate. Our results can explain debt prices across countries following the 2008 financial crisis, and also provide a theory of “original sin.”